Republic of Congo : Joint Advisory Note on the Poverty Reduction Strategy Paper; Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This Joint Staff Advisory Note reviews the first annual progress report (APR) on implementation of the Poverty Reduction Strategy (PRS) in the Republic of Congo. The adoption of Congo's first full Poverty Reduction Strategy Paper was an important step toward consolidating macroeconomic stability and improved political and economic governance. The APR takes stock of the first year of PRS monitoring and implementation, and provides an update on the poverty diagnosis, and elaborates on the central aspects of the strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet